Perlindungan Hak Ahli Waris terhadap Penguasaan Sepihak Harta Warisan oleh Salah Satu Ahli Waris dalam Analisis Putusan Nomor 0563/Pdt.G/2016/PA.JP - Rayi Kharisma Rajib; Fadila Casie Musafa; Safa Kaila Fitria (CV. ITTC INDONESIA, 2026)
The unilateral control of inherited property by one or several heirs still frequently occurs in society and causes losses to other heirs. This study aims to analyze the legal protection of heirs’ rights and the judge’s considerations in Decision Number 0563/Pdt.G/2016/PA.JP. The method used is normative legal research with statutory and case approaches. The results show that the legal protection of heirs’ rights is regulated in the Compilation of Islamic Law (KHI) and the Indonesian Civil Code. In this decision, the judge considered the control of the inherited property by three out of nine heirs without the consent of the others as an unlawful act. The decision is considered to have provided fair legal protection through the restoration of heirs’ rights and legal certainty, although such protection is repressive in nature.